Cooling pad temperature monitoring system using Arduino (CPTM) / Noor Azah Samsudin ... [et al.] - Samsudin, Noor Azah; Nordin, Nor Amirul Amri; Aripin, Muhammad Syariff; Ahmad Khalid, Shamsul Kamal (Universiti Teknologi MARA, Kedah, 2019)
Cooling pad is used to reduce temperature of laptop to avoid overheating problem. However, the existing cooling pad is prone to various limitations: fixed voltage in the hardware component and lacked of computer-based temperature monitoring functions. This project is to overcome the overheating problem by implementing a computer-based prototype in the cooling pad temperature monitoring system using Arduino. In this project, real-time temperature of laptop is captured. A Graphical User Interface (GUI) is also implemented to observe temperature values captured from the laptop. The temperature values are displayed in graph and tabular form. The performance of the proposed cooling pad with computer-based monitoring application is evaluated against two other types of existing cooling pad systems. The results have shown that the temperature values can be monitored clearly with the proposed GUI. Indeed, the proposed cooling pad system has the potential to achieve lower temperature faster than the rest of the existing cooling pad systems. Such results suggest that life expectancy of a laptop can also be increased because the overheating problem can be avoided significantly.